Magnetic Resonance Imaging in Primary Sclerosing Cholangitis - Aldona Wybraniec-Zaręba; Julia Tuchalska-Czuroń; Gabriela Półtorak-Szymczak; Mariusz Furmanek; Jerzy Walecki; Katarzyna Sklinda (Wiedza Medyczna, 2021)
Primary sclerosing cholangitis (PSC) is a chronic liver disease in which there are inflammation and scarring of the bile ducts leading to fibrosis, destruction and narrowing of the bile ducts, resulting in cholestasis. In the long run, PSC can cause liver cirrhosis and failure. In clinical practice, the diagnosis of PSC is generally based on blood tests and imaging studies (currently preferably magnetic resonance cholangiopancreatography). To make a diagnosis of PSC it is necessary to exclude secondary causes of sclerosing cholangitis. The most common MRI features of PSC concerning bile ducts are: bile duct dilatation, beading, extrahepatic bile duct stenosis, wall enhancement and thickening. The most common MRI features of PSC concerning hepatic parenchyma are: rounded shape of the liver caused by hypertrophy of caudate lobe and left liver lobe, atrophy of the right lobe, enlargement of portal and/or portacaval lymph nodes, peripheral parenchymal inflammation, wedge-shaped confluent fibrosis, heterogeneity of the liver parenchyma, periportal oedema, cirrhosis with indirect signs of portal hypertension such as splenomegaly, ascites and collateral vasculature.